Peran Desa Bedahlawak sebagai Desa Ramah Anak dalam Penyelenggaraan Perlindungan Anak - Asri Gresmelian Eurike Hailitik; Lestia Inggrid Maharani; Veronika Yuliani Moo; Tomy Michael (LITERATUS, 2023)
This research aims to explore the fulfillment of children's rights through child-friendly villages. Children will become the next generation of the nation, therefore it is time for the state to guarantee child protection. To realize this, one of them is by forming a Child-Friendly City that will help realize the success of legal protection in Indonesia. The child's relationship and its protection are close to parents, families, communities, governments, local governments, and the state. Every effort must be made to protect children so that they can live healthy lives and participate in society according to the wishes of their parents. This is known as child protection. The people of Bedahlawak Village began to realize how important it is to fulfill and protect children's rights. This village began to focus on improving child friendliness in the form of protection, participation, and fulfillment of children's rights. This research focuses on qualitative research methods where there is analysis, observation, visual and literature study. Then this study uses a literature study of previous research related to the research theme. This research focuses on the object of anah-friendly villages about the fulfillment of children's rights in Bedahlawak village, Jombang Regency. The results of this research through Child-Friendly Villages have an active role in the creation of Child-Friendly Villages, namely the achievement of Child-Friendly cities or districts so that protection of children's rights that are expected to be protected will be realized.